Should primary anastomosis be considered more? A retrospective analysis of anastomotic complications in young children - Laurens D. Eeftinck Schattenkerk; Gijsbert D. Musters; Wouter J. de Jonge; L.W. (Ernest); Joep PM Derikx (BMJ Publishing Group, 2023)
Objective Little is known about intestinal anastomotic leakage and stenosis in young children (≤3 years of age). The purpose of this study is to answer the following questions: (1) what is the incidence of anastomotic stenosis and leakage in infants? (2) which surgical diseases entail the highest incidence of anastomotic stenosis and leakage? (3) what are perioperative factors associated with anastomotic stenosis and leakage?Methods Patients who underwent an intestinal anastomosis during primary abdominal surgery in our tertiary referral centre between 1998 and 2018 were retrospectively included. Both general incidence and incidence per disease of anastomotic complications were determined. Technical risk factors (location and type of anastomosis, mode of suturing, and suture resorption time) were evaluated by multivariate Cox regression for anastomotic stenosis. Gender and American Society of Anaesthesiology (ASA) score of ≥III were evaluated by χ2 test for anastomotic leakage.Results In total, 477 patients underwent an anastomosis. The most prominent diseases are intestinal atresia (30%), Hirschsprung's disease (29%), and necrotizing enterocolitis (14%). Anastomotic stenosis developed in 7% (34/468) of the patients with highest occurrence in necrotizing enterocolitis (14%, 9/65). Colonic anastomosis was associated with an increased risk of anastomotic stenosis (hazard ratio (HR) =3.6, 95% CI 1.8 to 7.5). No technical features (type of anastomosis, suture resorption time and mode of suturing) were significantly associated with stenosis development. Anastomotic leakage developed in 5% (22/477) of the patients, with the highest occurrence in patients with intestinal atresia (6%, 9/143). An ASA score of ≥III (p=0.03) and male gender (p=0.03) were significantly associated with anastomotic leakage.Conclusions Both anastomotic stenosis and leakage are major surgical complications. Identifying more patient specific factors can result in better treatment selection, which should not solely be based on the type of disease.